Fluoropyrimidine adjuvant chemotherapy leads to long-term impact on coronary arteries, blood cell profile and iron in colorectal cancer survivors - Ivana Iveljic; Lejla Alidzanovic Nurkanovic; Alisa Krdzalic; Dunja Aksentijevic (Medicinski glasnik, 2025)
Aim: To assess whether colorectal carcinoma (CRC) survivors 5 years post-fluoropyrimidine (5-fluorouracil and capecitabine) chemotherapy (ChemT) have increased presence of subclinical coronary artery disease (CAD), lower iron and altered blood cell composition. Methods: This prospective, 2 year, single-center study used invasive coronary angiography to detect the presence of CAD among ChemT (N=45) and control group patients (age, gender-matched, cancer-naïve (N=45). Full blood count and iron levels were compared between two groups. Results: Coronary angiography in 90 patients (mean age 65±7 years; 60% male) identified significantly higher presence of CAD in CRC ChemT patient group compared to control: 80% vs. 55 % (p=0.013). CRC ChemT patients had lower red blood cell count (4.45± 0.56 vs. 4.68± 0.50 x10 9 /L; p=0.044), platelet count (214.18±50.99 vs. 251.00 ±156.40 x10 9 /L; p=0.002) and white blood cell count (5.50 ±1.62 vs. 7.67±1.72 x10 9 /L; p=0.000). Mean corpuscular hemoglobin concentration was higher in CRC ChemT patients (342.11 g/L ±15.74 vs. 336.42 g/L ±10.29: p=0.046), and iron deficiency was more prevalent (ChemT20.40 µmol/L ±3.891vs. control 23.37 µmol/L ±4.10: p=0.001). Conclusion: Our study shows that among CRC survivors who underwent 5-FU and capecitabine therapy there is a significantly higher prevalence of CAD accompanied by long-term impairment in blood erythropoiesis. Keywords: : coronary artery disease, coronary angiography, erythropoiesis
Keywords: coronary artery disease; coronary angiography; erythropoiesis